Interplay Between Microglia and Alzheimer’s Disease—Focus on the Most Relevant Risks: APOE Genotype, Sex and Age - Chen, Yanting; Hong, Tingting; Chen, Feng; Sun, Yuanhong; Wang, Yan; Cui, Lili (Frontiers in Aging Neuroscience, 2021)
As the main immune cells of the central nervous system (CNS), microglia regulate normal development, homeostasis and general brain physiology. These functions put microglia at the forefront of CNS repair and recovery. Uncontrolled activation of microglia is related to the course of neurodegenerative diseases such as Alzheimer’s disease. It is clear that the classic pathologies of amyloid β (Aβ) and Tau are usually accompanied by the activation of microglia, and the activation of microglia also serves as an early event in the pathogenesis of AD. Therefore, during the occurrence and development of AD, the key susceptibility factors for AD—apolipoprotein E (APOE) genotype, sex and age—may further interact with microglia to exacerbate neurodegeneration. In this review, we discuss the role of microglia in the progression of AD related to the three risk factors for AD: APOE genotype, sex and aging. APOE-expressing microglia accumulate around Aβ plaques, and the presence of APOE4 may disrupt the phagocytosis of Aβ aggregates and aggravate neurodegeneration in Tau disease models. In addition, females have a high incidence of AD, and normal female microglia and estrogen have protective effects under normal conditions. However, under the influence of AD, female microglia seem to lose their protective effect and instead accelerate the course of AD. Aging, another major risk factor, may increase the sensitivity of microglia, leading to the exacerbation of microglial dysfunction in elderly AD. Obviously, in the role of microglia in AD, the three main risk factors of APOE, sex, and aging, are not independent and have synergistic effects that contribute to the risk of AD. Moreover, new microglia can replace dysfunctional microglia after microglial depletion, which is a new promising strategy for AD treatment.